Penilaian konsumsi nutrisi dan performa penggemukan sapi jantan Simmental Persilangan pada waktu pemberian pakan yang berbeda - Theo Mahiseta Syahniar; Dwi Agus Setiawan; Mira Andriani (Universitas Bengkulu, 2023)
This study aimed to determine nutrient consumption, body weight gain, feed conversion, and feed efficiency of Simmental crossbred bulls through different feeding management specifically for levels of time on feed offered. Nine bulls were allocated on three different level treatments and three replicates. They were T0=feeding whole concentrate first in the morning then offering whole chopped forages after 6 hours later; T1=feeding half of the concentrate first then offering half of the chopped forages after 2 hours later in the morning and afternoon; T2=feeding half of the concentrate and chopped forages simultaneously in the morning and afternoon. Bulls were fed twice daily and had free access to drinking water ad libitum. Parameters observed were nutrient consumption, daily gain, feed conversion and efficiency. Data were analyzed using ANOVA and further analysis by DMRT for the significant parameter. The results showed that the treatment of different feeding management presented significantly different (P<0.05) on nutrient consumption; however, it had no effect (P>0.05) on daily gain, feed conversion, and feed efficiency. Feed-offered time differences affected nutrient consumption but did not alter the concentrate and forage ratio consumed or cattle performances.